The Role of Kh. Noer Alie in the Development of Islamic Education at the Attaqwa Islamic Boarding School - Mudzakir (Sinergi International Journal of Education, 2023)
This research aims to determine the role of KH. Noer Alie in developing Islamic education and how he implemented this role at the Al-Attaqwa Ujung Harapan Islamic boarding school, North Bekasi. The method used in this research is descriptive qualitative, by describing circumstances, conditions, situations, events and activities carried out by KH. Noer Alie in relation to the development of Islamic education at the Attaqwa Ujung Harapan Islamic boarding school, North Bekasi. The role of KH. The Noer Alie researched here is about the development of Islamic education at the Attaqwa Ujung Harapan Ujung Bekasi Islamic boarding school in terms of the institutions he founded and ideas and ideas related to the development of education itself. Data analysis techniques obtained and studied from the results of interviews, observations and documentation at the research site are then processed, studied and described into a conclusion. The research results that can be concluded are KH. Noer Alie built an Islamic educational institution and he became an innovator in providing ideas and ideas that could be implemented at the Attaqwa Ujung Harapan Bekasi Islamic boarding school. In building Islamic educational institutions he built formal (school) and non-formal (cottage) education. The existence of formal and non-formal educational institutions is intended so that students are not only intelligent in terms of religion, but students are also intelligent in general science and technology which is currently developing.